Konversi Peradaban Arab Jahiliyah Ke Peradaban Islam - Elwahdiyah, Arifah; Edi Yusrianto (CV. ITTC INDONESIA, 2025)
The Jahiliyah civilization was characterized by social instability, tribal fanaticism, moral decadence, economic injustice, low levels of education, and spiritual decline. These conditions indicate that Arab society did not yet have a civilized and just way of life. The arrival of Islam brought about major changes in Arab society as a whole. This study aims to describe the conditions of the Jahiliyah Arab civilization before Islam, analyze the process of value transformation brought by Islam, and identify its impact on the development of Islamic civilization and the world. The research method used is library research by analyzing various literature sources related to the conditions of the Jahiliyah Arab civilization and the changes brought about by Islamic teachings. The results show that Islam brought fundamental changes in the aspects of faith, morals, social, economic, and strong scientific. This study confirms that the conversion from Jahiliyah civilization to Islamic civilization was a major revolution that not only transformed Arab society but also influenced the direction of the development of world civilization. The transformation of Islamic values ​​​​has proven to produce a civilized, humane, and just society that remains relevant to human life until the modern era.